Work Related Discomforts from Perception of Optometrists, in Saudi Arabia - Al-Anzi, Hessa (Arab Journal for Sciences and Research Publishing, 2015)
Work-related discomfort is a growing problem around the world that affects not only the health and well-being of optometrists, but also the productivity. Work-related discomfort arises where work demands of various types and combinations exceed the person’s capacity and capability to cope. In addition, stress can be caused by various events. For example, a person might feel under pressure if the demands of their job (such as hours or responsibilities) are greater than they can comfortably manage. Work-related physical discomfort reported in Saudis optometrists. The purpose of this paper is to explore the personal consequences of work-related discomfort. 129 optometrists with self-reported work-related discomfort participated in a 30-minute telephone or face-to-face interview related to ergonomics and physical comfort. The questionnaire gathered demographic data as well as information on occurrence of musculoskeletal complaints in the previous 12 months. Four avenues were investigated; namely, description of discomfort, non-work contributing factors, whether the participant has ever stopped work due to discomfort, and the treatments accessed to alleviate discomfort. These data were subject to qualitative and quantitative analyses. Reported discomfort ranged from mild to severe. 21participants (16.3) hospitalized because of discomfort. Moreover, 108 participants (83.7) never been hospitalized because of discomfort. In addition, the results highlighted that 110 participants (85.3%) ever had to change jobs or duties because of this discomfort.19 participants (14.7%) never had to change jobs or duties because of this discomfort. Although their work related discomfort, 62.8% expressed that their discomfort did not prevent them from performing certain tasks. While 37.2% % expressed that their discomfort prevented them from performing certain tasks.